2020
DOI: 10.4314/aas.v17i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Lower Urinary Tract Symptoms Among Patients with Prostatic Diseases

Abstract: Background: Incidence of symptomatic prostatic diseases increases with age. Nocturia disturbs sleep. We set out to determine the quality of sleep and severity of lower urinary tract symptoms (LUTS) and bother score in patients with benign prostatic hyperplasia (BPH) and carcinoma of the prostate (CAP). Methods: A cross-sectional study of new patients seen in the urology outpatient clinic with bladder outlet obstruction (BOO) from either BPH or CAP over a period of 18 months. Patients were intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…A previous study indicates that increased age, gender, physical activity, alcohol consumption, smoking, and obesity are associated with increased severity of leading to a higher risk of sleep disturbance. 40 Hence, our findings accord with the early evidence suggesting that suffering from LUTS and symptomatic BPH diseases may induce sleep disturbance resulting in the poor sleep quality 22 and quality of life. 23 However, individual characteristics may contribute to LUTS due to BPH in this study; after controlling the prominent confounding factors-age and comorbidities-our findings help to gain more understanding of the impact of falls and sleep quality on quality of life, which is congruent with the health-related quality of life model of Ferrans et al 12 that described linkage among concepts on quality of life.…”
Section: Pacific Rim Int J Nurs Res • July-september 2023supporting
confidence: 89%
See 2 more Smart Citations
“…A previous study indicates that increased age, gender, physical activity, alcohol consumption, smoking, and obesity are associated with increased severity of leading to a higher risk of sleep disturbance. 40 Hence, our findings accord with the early evidence suggesting that suffering from LUTS and symptomatic BPH diseases may induce sleep disturbance resulting in the poor sleep quality 22 and quality of life. 23 However, individual characteristics may contribute to LUTS due to BPH in this study; after controlling the prominent confounding factors-age and comorbidities-our findings help to gain more understanding of the impact of falls and sleep quality on quality of life, which is congruent with the health-related quality of life model of Ferrans et al 12 that described linkage among concepts on quality of life.…”
Section: Pacific Rim Int J Nurs Res • July-september 2023supporting
confidence: 89%
“…39 Although decreased sleep quality depends on the severity of LUTS, exacerbating BPH symptoms may interfere with the sleep patterns in older adults with LUTS. 22 As expected, comparing PSQI mean scores, our findings revealed that the participants with LUTS due to BPH had poorer sleep quality than in a previous study. The poorer sleep quality may be partly explained by personal factors-history of alcohol consumption, smoking, obesity, comorbidities, and surgery-of the participants that might influence worsening LUTS and BPH symptoms.…”
Section: Pacific Rim Int J Nurs Res • July-september 2023supporting
confidence: 84%
See 1 more Smart Citation
“…As the age advances, this gland becomes susceptible to many diseases such as inflammation, infections, benign enlarge-ment, and neoplasia. These disorders are an important cause of frequent urinary complaints such as poor flow, nocturia, frequency, and urgency; commonly referred to as lower urinary tract symptoms (LUTS) in the ageing male population 1 . Lower urinary tract symptoms negatively influence the patient's quality of life and these patients reported depressive symptoms and diminished sexual activity more frequently than those without lower urinary tract symptoms diminish.…”
Section: Introductionmentioning
confidence: 99%